Assemblage theory and the uses of classical reception: the case of Aristotle Knowsley's Oedipus. (28th September 2019) - Ward, Marchella
Abstract: The metaphors that we use to describe the relationships between texts often carry within them limitations on the relationships that they figure. Classical reception is perhaps the most dominant of these metaphors, structuring the way readers understand the relationships between texts. This is particularly problematic in the early modern period where it is often difficult to account for the relationships between texts using traditional models of influence (a problem that is further amplified in performance). This article uses the example of an Oedipus play written by Aristotle Knowsley sometime between 1596 and 1603 to ask whether thinking about what we more often call 'receiving texts' as 'assemblages' could offer the study of classical reception a way to confront the restrictions placed upon it by the linearity of literary history. Knowsley's text — when it is discussed at all — is usually considered to be an amalgamation of Neville's translation of Seneca's Oedipus (1563) and Newton's Thebais (1581), but this restrictive reading, based on assumptions latent in the metaphor 'classical reception', excludes a number of texts that participate in productive relationships with the play.